ANALISIS FLUKTUASI HARGA TELUR AYAM RAS DI KOTA KENDARI - Ramadhan, Muhammad Akbar; Bafadal, Azhar; Zani, Munirwan (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The purpose of this study was to analyze the price fluctuations of chicken eggs in Kendari City. This study was conducted in Kendari City. The location was determined intentionally (purposively) considering that Kendari City is one of the centers of chicken egg sales. The study was conducted in October 2023–July 2024. The types and sources of data used in this study are secondary data, namely time series data on chicken egg prices from 2015 to 2022. The collection technique in this study is a literature study. The variables in this study are the price of chicken eggs in Kendari City from 2015 to 2022. The data analysis used to analyze the price fluctuations of chicken eggs in Kendari City is the Coefficient of Variation (CV). The results of the study show that the price fluctuations of chicken eggs in Kendari City in the last eight years, from 2015 to 2022, are included in the moderate category, namely with a coefficient of variation or CV of 6%. The highest price of chicken eggs in Kendari City occurred in 2017, which was Rp 58,538/kg. While the lowest price of chicken eggs in Kendari City occurred in 2015, which was Rp 21,616/kg.